Influence Motivation Work And Environment Work To Job Satisfaction, Work Discipline And Performance PT employees. Indonesian Railways (Persero) DAOP IX Jember - Dinarizka Leksi Primandaru; Diana Sulianti K. Tobing; Dewi Prihatini (International Journal of Management Research and Economics, 2024)
In an enterprise, employees hold a very important role in an effort to achieve a goal. As motors activity in the company that this objective could be achieved by both, employees should be encouraged to be more aggressive and better at working. This research attempts to analyze and he knows and proves empirically the influence of direct and indirect work motivation and workplace on the performance of them through work satisfaction and discipline work in PT. Kereta Api Indonesia (Persero) Daop IX Jember. This research can be classified as explanatory research that uses sample technique proportionate sampling. The population research is all employees in PT. Indonesian Railways (Persero) Daop IX Jember totaling 163 min. The samples for every sub population searchable by means of dividing sub population with the number of the population multiplied by large sample members. Total included in this study were 118 employees that the data was undertaken by the spread of the questionnaire to respondents that were employees of PT. Indonesian Railways (Persero) Daop IX Jember. Data mixed using analysis structural equation model using IBM spss amos 20 software. The results of the study this proves that all hypotheses accepted that motivation influences directly or indirectly on work performance through satisfaction and workplace also affected directly or indirectly on performance through employee work discipline .